anonymous
  • anonymous
PLEASE HELP, IM SO CONFUSED. Factoring Polynomials 2x^2 + 15x - 38
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
misssunshinexxoxo
  • misssunshinexxoxo
Simplifying 2x2 + 15x + -38 = 0 Reorder the terms: -38 + 15x + 2x2 = 0 Solve this ^
anonymous
  • anonymous
15x + 2x^2=38?
misssunshinexxoxo
  • misssunshinexxoxo
We had to reorder them Solving for variable 'x'. Factor a trinomial. (-19 + -2x)(2 + -1x) = 0

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
how did you get that??
misssunshinexxoxo
  • misssunshinexxoxo
Simplifying -19 + -2x = 0 Solving -19 + -2x = 0 -19 + 19 + -2x = 0 + 19 Combine like terms: -19 + 19 = 0 0 + -2x = 0 + 19 -2x = 0 + 19 Combine like terms: 0 + 19 = 19 -2x = 19 Divide each side by '-2'. x = -9.5 Simplifying x = -9.5
anonymous
  • anonymous
thats not what the question is asking. I know the answer its (2x+19)(x-2) but idk how do get there
misssunshinexxoxo
  • misssunshinexxoxo
2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Looking for something else?

Not the answer you are looking for? Search for more explanations.